2019
DOI: 10.1186/s13293-019-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting senescence improves angiogenic potential of adipose-derived mesenchymal stem cells in patients with preeclampsia

Abstract: Background Preeclampsia is a pregnancy-specific hypertensive disorder characterized by impaired angiogenesis. We postulate that senescence of mesenchymal stem cells (MSC), multipotent cells with pro-angiogenic activities, is one of the mechanisms by which systemic inflammation exerts inhibitory effects on angiogenesis in preeclampsia. Methods MSC were isolated from abdominal fat tissue explants removed during medically indicated C-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 37 publications
3
53
0
Order By: Relevance
“…In addition, the present study revealed that McP1 reversed the progression of NPMSc differentiation into cartilage and inhibited SIRT1-induced cell apoptosis. It was previously reported that in NPMScs, McP1 expression is notably reduced (33). SIRT1 overexpression downregulates McP1, whereas the loss of SIRT1 increases McP1 expression, indicating a negative association between these two proteins (34).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the present study revealed that McP1 reversed the progression of NPMSc differentiation into cartilage and inhibited SIRT1-induced cell apoptosis. It was previously reported that in NPMScs, McP1 expression is notably reduced (33). SIRT1 overexpression downregulates McP1, whereas the loss of SIRT1 increases McP1 expression, indicating a negative association between these two proteins (34).…”
Section: Discussionmentioning
confidence: 89%
“…Senescent cells can accumulate at aetiological sites of multiple diseases throughout the lifespan. For example, in humans, senescent cells accumulate in adipose tissue in diabetes and obesity, in the hippocampi and frontal cortex in Alzheimer's disease (AD), the substantia nigra in Parkinson's disease (PD), bone and marrow in age-related osteoporosis, lungs in idiopathic pulmonary fibrosis, liver in cirrhosis, retinae in macular degeneration, plaques in psoriasis, kidneys in diabetic kidney disease, endothelium in pre-eclampsia, and the heart and major arteries in cardiovascular disease, amongst many other conditions [6,7,13,19,23,[70][71][72][73][74][75][76][77][78][79][80].…”
Section: Cellular Senescencementioning
confidence: 99%
“…In addition, the SASP of senescent cells seems to contribute to the initiation of parturition. However, cellular senescence might also have a role in the impaired angiogenesis associated with preeclampsia 137 . Thus, for reproductive function, cellular senescence could represent an example of antagonistic pleiotropy, whereby it contributes to proper fetal development and timely parturition during the reproductive years but also to the risk of pre-eclampsia and a decline in ovarian function with ageing 134 .…”
Section: Cellular Senescence In Reproductive Ageingmentioning
confidence: 99%
“…• Frailty and impaired ambulation in elderly women 143 • Progeroid syndromes in children 82,101,144 • Pre-eclampsia 137 • Macular degeneration and other eye diseases 145 • Skin conditions, including psoriasis, scleroderma, melanocytic naevi, actinic keratosis, non-healing skin wounds and other skin disorders 146 • Idiopathic pulmonary fibrosis 51,102 • Chronic obstructive pulmonary disease 147 • Inducing accumulation of senescent cells causes the phenotype.…”
Section: Key Points •mentioning
confidence: 99%